(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study investigated the classroom managers’ technological pedagogical content knowledge (TPACK) during the implementation of remote schooling. It is especially interested in learning about their changing roles and experiences with the TPACK model. This study employs a descriptive phenomenological approach. Through purposive sampling, ten (10) elementary educators participated. Teachers’ personal experiences were collected through in-depth online interviews via Google Meet and Messenger. Colaizzi’s data analysis approach was utilized in analyzing the gathered data. The results revealed that the changing role of educators employs positive and negative results in the materials, process, feedback, students, and parents. Also, educators enhance their role by being effective goal-setters, efficient communicators, implementers and planners, lifelong learners, and assessment experts in coping with diverse challenges. Lastly, it shows the status of TPACK integration, which helps elementary educators to be efficient. Moreover, educators used TPACK as their roles changed during the COVID-19 Pandemic. It is then an implied training proposal for adequate technological, pedagogical, and content knowledge in minor emergencies to build up educators’ knowledge and further study to identify issues and barriers for educators to teach in a pandemic effectively.